2017
DOI: 10.1038/ncomms15538
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic non-crystalline U(IV) revealed as major component in uranium ore deposits

Abstract: Historically, it is believed that crystalline uraninite, produced via the abiotic reduction of hexavalent uranium (U(VI)) is the dominant reduced U species formed in low-temperature uranium roll-front ore deposits. Here we show that non-crystalline U(IV) generated through biologically mediated U(VI) reduction is the predominant U(IV) species in an undisturbed U roll-front ore deposit in Wyoming, USA. Characterization of U species revealed that the majority (∼58-89%) of U is bound as U(IV) to C-containing organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 65 publications
(107 reference statements)
2
69
0
Order By: Relevance
“…Amorphous UO 2 may be the result of such processes. Indeed, besides complexation and sorption, a third mechanism was recently proposed by [52]: the formation of U(IV) biofilms that evolve into biogenic non-crystalline U(IV) compounds. Thus, using EXAFS (Extended X-ray Absorption Fine Structure) spectroscopy data, these authors revealed the role of microorganisms in the reduction of U(VI) and the formation of disseminated U(IV) in organic matter, acting both as nutrient and as trap.…”
Section: Uranium Trapping Processes Involving Organic Matter At Zoovcmentioning
confidence: 99%
“…Amorphous UO 2 may be the result of such processes. Indeed, besides complexation and sorption, a third mechanism was recently proposed by [52]: the formation of U(IV) biofilms that evolve into biogenic non-crystalline U(IV) compounds. Thus, using EXAFS (Extended X-ray Absorption Fine Structure) spectroscopy data, these authors revealed the role of microorganisms in the reduction of U(VI) and the formation of disseminated U(IV) in organic matter, acting both as nutrient and as trap.…”
Section: Uranium Trapping Processes Involving Organic Matter At Zoovcmentioning
confidence: 99%
“…To answer these questions, substantial effort is now required to locate, verify, analyze, and integrate geological records of the deep biosphere in deep time. Recent work has begun to reveal geologically ancient chemical and isotopic signatures of microbial metabolism in the subsurface; fluctuations in these signals through sedimentary rock successions can in principle reveal changes in deep microbial activity over timescales of at least millions of years . Here, we focus instead on the traditional subject matter of palaeobiology: body fossils—the mineralized or organically preserved remnants of organismal structures.…”
Section: Introduction: What Lies Beneath?mentioning
confidence: 99%
“…Few reported cellular or molecular fossils pass all three tests unequivocally, and most candidates represent subseafloor environments 7 10 . Microbially mediated diagenetic phenomena on palaeo-redox fronts offer a potentially powerful alternative record that could extend to continental settings 11 , 12 . Of longstanding interest in this connection are reduction spheroids, which are very common mm–dm-scale bleached spots found most commonly (but not exclusively) in Proterozoic–Phanerozoic red beds, i.e., sedimentary rocks deposited in oxidising terrestrial environments and rich in early diagenetic haematite 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“… 19 ). Thus, uranium phases (both mineralised and non-mineralised) in reduction spheroids and analogous low-temperature redox-front uranium deposits have been shown 12 , 19 to contain predominantly U(IV). Uranium reduction can occur via many pathways 18 , 25 , both abiotic (coupled to the oxidation of various aqueous, mineral, and organic species) and biotic (i.e., enzymatic catalysis by chemolithotrophic microorganisms capable of facultatively utilising U(VI) as an electron acceptor, including iron- and sulphate-reducers).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation